2020
DOI: 10.52547/jhc.22.2.138
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nurses' Self-efficacy and Job Expectations with Patient Safety Culture

Abstract: Background & aim: Patient safety is one of the most important components of care quality. Nurses' self-efficacy has been introduced as a factor affecting the quality of care and job expectations which in turn affects nurse's job behavior and attitude. Thus, the purpose of this study was to determine the relationship between self-efficacy and job expectations of nurses with patient safety culture. Methods: This study was a correlational descriptive study. 210 Nurses in educational hospitals affiliated to Shahre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…This result is consistent with a study done by Bahreini Brujeni and Alavi. 54 They reported that the mean self-efficacy scores among nurses was 58.03. However, Norouzinia et al 55 reported a moderate self-efficacy of nurses.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with a study done by Bahreini Brujeni and Alavi. 54 They reported that the mean self-efficacy scores among nurses was 58.03. However, Norouzinia et al 55 reported a moderate self-efficacy of nurses.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports from the Ministry of Health in Iran, billions of Tomans are spent annually on treating and caring for patients who experience mistakes or medical errors, including medication errors. Studies have shown that nearly onethird of adverse drug reactions occur due to medication errors (7)(8)(9)(10)(11)(12)(13). Therefore, medication errors are considered an important indicator in determining patient safety in healthcare facilities (14,15).…”
Section: Introductionmentioning
confidence: 99%